Pengaruh Pemahaman Perpajakan, Kebijakan Pemerintah, dan Implementasi Teknologi Terhadap Efektivitas Tax Planning - Fitria Saumaningsih (Eastasouth Institute, 2023)
Tax Planning Concept Is the concept in taxation discipline that aims to manage the tax based on the rule. Tax Planning ain’t mean to push the taxpayer to avoid the tax but how to push them to comply with the tax rule and create administration compliance and simplification. PT CPE Cell International was using the tax planning concept in their business to create the effectivity of tax management where the effectivity is determined by Understanding the Tax Rule, Government Policy, and Technology Implementation.